2020
DOI: 10.1097/sla.0000000000003808
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of the Risk Analysis Index as a Prospective Frailty Screening Tool within a Multi-practice, Multi-hospital Integrated Healthcare System

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 31 publications
0
94
0
Order By: Relevance
“…39,40 By comparison, preoperative frailty screening using validated instruments has been found both efficient and effective for identifying potentially vulnerable adults and such tools are also being developed in pediatric patients. [41][42][43] As such, more objective preoperative assessment tools should be developed and used to aid the preoperative identification of patients who may be at risk for adverse postoperative outcomes, like FTR. There are several limitations to consider when interpreting our data.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 By comparison, preoperative frailty screening using validated instruments has been found both efficient and effective for identifying potentially vulnerable adults and such tools are also being developed in pediatric patients. [41][42][43] As such, more objective preoperative assessment tools should be developed and used to aid the preoperative identification of patients who may be at risk for adverse postoperative outcomes, like FTR. There are several limitations to consider when interpreting our data.…”
Section: Discussionmentioning
confidence: 99%
“…Brief survey instruments, such as the 14-item Risk Analysis Index (RAI), have shown encouraging prognostic ability with respect to mortality and post-operative complications. 13,16 Automated approaches to risk stratification leveraging the Electronic Health Record (EHR) are still desirable for two reasons. First, survey instruments like the RAI are currently performed after referral for surgery, and so are less useful for shared decision-making concerning whether or not to refer to surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Skin cancer excisions do not typically require general anesthesia, deep sedation, or large fluid shifts; however, studies have found that when frail patients undergo low-risk procedures, they tend to have a higher mortality rate than their healthier counterparts. 15 Frailty is a concept that identifies patients who are at increased risk of dying in 6 to 60 months due to a decline in their physical reserve. Frail patients have increased rates of perioperative mortality and complications.…”
Section: Discussionmentioning
confidence: 99%